Connecting user emotions and User Experience (UX) among university students during open distance learning - Zan Azma, Nasruddin; Aida Wati, Zainan Abidin; Nor Hapiza, Mohd Ariffin; Mohd Khairul Azmi, Hassan; Rahmah, Mokhtar (Institute of Electrical and Electronics Engineers Inc., 2023)
A catastrophic event such as the coronavirus pandemic (COVID -19) could have an impact on the global economy and on people's lives. When the virus COVID -19 began to spread uncontrollably in late February 2020, some schools and universities in the affected countries were closed. The universities have no choice but to use open distance learning (ODL) to stay in business. Therefore, the platform used for ODL should be effective and practical to optimize the learning experience of students. The important aspects include accessibility, practicality, ease of use and usefulness of the platform used. Furthermore, the learning experience would affected the students' emotions in either positive or negative ways. Hence, the aim of this study was to identify the factors that influence the user experience during ODL and how the emotions is connected to the user experience. The results of the multiple linear regression analysis of this study showed that accessibility was the most important factor influencing user experience, followed by desirability and usability of the ODL learning platform. However, the experience was not influenced by gender, age or the institution where the students were enrolled. Besides, poor internet connection causes the negative emotions such as tensed, frustrated and bored to the students and consequently found out that the learning is no longer useful, while positive emotions such as happy and excited would be achieved when the students could appreciate the usability of the ODL platform.